Literasi Anak Usia Dini: Optimalisasi Penggunaan Perpustakaan Taman Kanak-Kanak - Asti Nur Hadianti; Atiasih Atiasih; Luluk Mukaromah; Zaharah Binti Awang; Zety Yusmira (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
Early childhood literacy is essential to children's cognitive and social development. A literacy environment helps build children's interests, including reading and writing. Reading readiness is very important so young children can develop a basic understanding of letters and sounds before formal learning at school. One practical approach to increasing early childhood literacy is to utilize kindergarten libraries. They are optimizing Kindergarten Libraries as a form of accommodating Early Childhood literacy. This research uses descriptive qualitative so that the author can describe in detail and interpret the data or symptoms obtained during the study, which was carried out at Kindergarten Pelita Hati Jember. Data collection techniques include interviews, observation, and documentation, with purposive determination of informants. So the informants chosen were the Principal, Class Teacher, Student Teacher, Library Teacher, and Students. The data analysis technique used is the Miles and Huberman data analysis technique. The research results show two developments in the optimization of the kindergarten library at Kindergarten Pelita Hati Jember, namely the development of book collections that are relevant to early childhood development and the development of new learning models. The library at Kindergarten Pelita Hati Jember is based on the tasks and functions of the library, including being a place for early childhood literacy activities. The room design and arrangement of books and other supporting equipment are very neatly arranged, with unique colours and a lovely study table.